The moderation of smart industry technology on the relationship between supply chain management practices and competitive advantage in the Dubai Electricity and Water Authority - Durmohamed, Yousef Abdulrahman Mohamed (2022)
This research aims to study the relationships between the different practices of supply change management, IR4 technology and smart factor, and competitive advantage in the Water and Electricity Authority in the Emirate of Dubai. This study suggested five independent variables of supply change management, which are aligning flows, integrating functions, coordinating processes, managing resources, and designing complex systems. While the dependent variable is competitive advantage and the moderating variable is the technology and smart factor. The target population in this study is the employees of the Water and Electricity Authority in the Emirate of Dubai, which is estimated at 11,000 employees, and the appropriate sample is 370 employees. Empirically, the final sample in the analysis includes 372 respondents, and the results showed that males represent 62.6%, age group of 36-45 years represents 30.9%, bachelor's degree respondents represent 66.1%, employees represent 53%, and experienced people with more than 12 years represent 31.2%. For the results of the descriptive analysis, it showed a good and very good positive evaluation with an approval rate of more than 70% for all the proposed variables. For the predictive model of competitive advantage, the results showed that the model predicted 58.6% of the variance in competitive advantage based on the five variables of supply change management. Coordinating processes of SCM has the highest impact (path coefficient = 0.461), resource management of SCM (path coefficient = 0.405), then aligning flows of SCM (path coefficient = 0.232), followed by designing complex systems of SCM (path coefficient = 0.227) and finally integrating functions of SCM (path coefficient = 0.113). Regarding the moderating impacts of smart industry technology on the five proposed relationships, the effect on the relationship between designing complex systems and competitive advantage is not statistically significant, while the effect onmthe other four relationships is statistically significant. Future studies can focus on expanding the proposed model by adding other relevant variables, as well as examining other dependent variables other than competitive advantage such as performance continuity.